Efeito da termorretificação na qualidade da superfície e na influência dos processos envolvidos no processo de lixamento da madeira de Pinus elliottii E Corymbia citriodora: Carlino Carvalho de Almeida. - - Almeida, Carlino Carvalho de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The sanding of wood is one of the most expensive processes in the industry and it is unknown the factors that influence the final quality of the parts. For this reason, studies involving different treatments in wood have been developed in order to provide a better surface finish, such as thermal treatments. The objective of this study was to investigate the influence of heat treatments in wood before the sanding process in the surface quality of the samples. The effects of heat treatments in wood sanding process was observed by comparing thermal treated and sanded samples with other samples that were only sanded. The species used in the study were Pinus elliottii and Corymbia citriodora. The sanding process used was a horizontal plane sanding with parallel direction to the fibers, aluminum oxide as abrasive material and two different particle size sandpaper P120 and P80. Firstly, the woods were thermal treated at 120, 160 and 200°C for two hours, and then, they were sanded and analyzed the surface quality of the parts with the parameter of roughness. For each temperature, six samples were thermal treated according to the particle size of sandpaper. It was also used six control samples for each grain size sandpaper, totaling 48 experimental units for each species under study. The effects of heat treatments in wood were analyzed by measuring the roughness, consumed power, acoustic emission, flatness, maximum temperature during sanding and analyses of images from microscope. With the results, it is concluded that the heat treatment significantly decreased the roughness of the wood of both species, which improved the surface finish of the parts

O lixamento da madeira é um dos processos mais caros na indústria e pouco se sabe sobre os fatores que influenciam na qualidade final das peças. Por esse motivo, estudos envolvendo diferentes tratamentos na madeira vêm sendo desenvolvidos, a fim de se proporcionar melhor acabamento superficial, como por exemplo a termorretificação. O objetivo deste trabalho foi verificar a influência da termorretificação da madeira antes do processo de lixamento sobre a qualidade superficial das peças. Foram utilizadas as espécies de Pinus elliottii e Corymbia citriodora. Para avaliar o efeito da termorretificação no processo de lixamento da madeira, foi comparado o acabamento superficial das madeiras lixadas com e sem tratamento térmico. O lixamento foi realizado utilizando duas granulometrias de lixa, P80 e P120, com grãos abrasivos de óxido de alumínio. O processo de lixamento foi executado mediante lixamento horizontal plano na direção paralela às fibras. Foram utilizados seis corpos de prova para cada granulometria de lixa. Inicialmente, os corpos de prova foram termorretificados à 120º C, 160º C e 200º C, por 2 horas, e em seguida foram lixados. Para a análise da qualidade superficial das peças foi empregado o parâmetro de rugosidade média. Ainda foram analisados a potência consumida, emissão acústica, planicidade, temperatura máxima durante o lixamento e imagens de superfície em microscópio. Com os resultados obtidos conclui-se que o tratamento térmico diminuiu significativamente a rugosidade da madeira de ambas espécies, facilitando o acabamento final das peças
Keywords: Termorretificação; Madeira - Propriedades térmicas; Tornearia; Pinus elliottii; Eucalipto; Wood